Evolution of cell populations in vitro: peculiarities, driving forces, mechanisms and consequences - Kunakh, V.A. (Вiopolymers and Cell, 2013)
This review outlines the major features and distinctions of cell populations, types and directions of selection in such populations. Population-genetic basis for cell adaptation to growth conditions in vitro is elucidated; in particular, peculiarities of genome evolution in the course of cell dedifferentiation and further cell adaptation to growth conditions in passaged culture are evaluated. Main factors of variation and selection in cell populations in vitro, influence of growth conditions on structure of cell populations and some regularities of cultured cells and regenerated plants are considered. Details of creation of stable cell lines-producers of biologically active substances are presented. Views and suppositions of author resulting from analysis of both literature data and own multiyear studies on cell population genetics are set forth. Among others are substantiated such key statements: cell culture in vitro presents dynamically-heterogeneous biological system, clone population, which is developing (evolving) as a result of major driving factors of evolution – variation, heredity, selection and drift of genes (genotypes); interaction between these processes determines the biological characteristics of each particular cell line grown in specific conditions; in adaptation of cells to growth conditions in vitro one can single out three periods: the initial population of isolated cells, the period of strain (cell line) formation and the established strain. The division into periods is determined by the type, direction and intensity of «natural» selection that acts in cell population. The formed (adapted to growth in vitro) strains are genetically heterogeneous, they are characterized by the presence of physiological and genetic homeostasis, which are mostly caused by the action of stabilizing selection; cultured cells of higher plants are able to synthesize practically all classes of secondary (specialized) compounds (alkaloids, steroids, terpenoids, etc.); any somatic cell with living (functionally active) nucleus during its isolation and further cultivation in tissue culture, as a result of the process of «somaclonal» variability occurring according to the N. I. Vavilov’s law of homologous series in hereditary variability, can restore in it’s descendants, including regenerated plants, the entire genetic polymorphism (or at least a significant part of it) characteristic of the plant’s species and may be even it’s genus. This provides an opportunity to preserve and restore the natural polymorphism in cultured cells and tissues in vitro. Розглянуто основні ознаки та відмінності клітинних популяцій, типи і напрями дії добору у таких популяціях. Висвітлено популяційно-генетичні основи адаптації клітин до умов росту in vitro, зокрема, проаналізовано особливості еволюції геному в процесі дедиференціювання клітин та подальшої адаптації їх до умов росту в пересадній культурі. Обговорено головні чинники мінливості та добору в клітинних популяціях in vitro, вплив умов вирощування на структуру клітинних популяцій та деякі закономірності мінливості культивованих клітин і рослин-регенерантів. Наведено особливості створення стабільних клітинних ліній – продуцентів біологічно активних речовин. Викладено погляди і припущення автора, сформовані в результаті аналізу як літературних даних, так і багаторічних власних досліджень з генетики клітинних популяцій. Серед низки інших обгрунтовано такі ключові положення: 1) культура клітин in vitro є динамічно-гетерогенною біологічною системою – клоновою популяцією, яка розвивається (еволюціонує) в результаті дії основних рушійних чинників еволюції – мінливості, спадковості, добору і дрейфу генів (генотипів); взаємодія цих процесів зумовлює біологічні особливості кожної конкретної клітинної лінії, що вирощується за конкретних умов. 2) У процесі адаптації клітин до умов росту in vitro виявляються три періоди: первинної популяції ізольованих клітин, становлення штаму (клітинної лінії), сформованого штаму; поділ на періоди визначається типом, напрямом та жорсткістю «природного» добору, що діє в клітинній популяції; сформовані (адаптовані до росту in vitro) штами є генетично гетерогенними, для них характерна наявність фізіологічного і генетичного гомеостазу, що визначається здебільшого дією стабілізуючого добору. 3) Культивовані клітини вищих рослин здатні до синтезу практично усіх класів сполук вторинного (спеціалізованого) обміну (алкалоїди, стероїди, терпеноїди та ін.). Будь-яка соматична клітина з живим (функціонально активним) ядром при її ізолюванні та подальшому вирощуванні за умов культури тканин внаслідок процесів «сомаклональної» мінливості, що відбуваються в рамках закону гомологічних рядів у спадковій мінливості М. І. Вавилова, може відновити у своїх нащадках, у тому числі серед рослин-регенерантів, увесь генетичний поліморфізм (або, принаймні, значну його частину), властивий даному виду, та, ймовірно, навіть і роду рослин. Це відкриває можливість збереження і відновлення природного поліморфізму в культурі клітин і тканин in vitro. Рассмотрены основные признаки и отличия клеточных популяций, типы и направления действия отбора в таких популяциях. Освещены популяционно-генетические основы адаптации клеток к условиям роста in vitro, в частности, проанализированы особенности эволюции генома в процесссе дедифференцирования клеток и последующей адаптации их к условиям роста в пересадной культуре. Обсуждены главные факторы изменчивости и отбора в клеточных популяциях in vitro, влияние условий выращивания на структуру клеточных популяций и некоторые закономерности изменчивости культивированных клеток и растений-регенерантов. Приведены особенности создания стабильных клеточных линий – продуцентов биологически активных веществ. Изложены взгляды и предположения автора, сформированные в результате анализа как литературных данных, так и многолетних собственных исследований по генетике клеточных популяций. Среди прочего обоснованы следующие ключевые положения: 1) культура клеток in vitro является динамично-гетерогенной биологической системой – клоновой популяцией, развивающейся (эволюционирующей) в результате действия основных движущих факторов эволюции – изменчивости, наследственности, отбора и дрейфа генов (генотипов); взаимодействие этих процессов обусловливает биологические особенности каждой конкретной клеточной линии, выращиваемой в конкретных условиях. 2) В процессе адаптации клеток к условиям роста in vitro выявляются три периода: первичной популяции изолированных клеток, становления штамма (клеточной линии), сформированного штамма; разделение на периоды определяется типом, направлением и жесткостью «природного» отбора, действующего в клеточной популяции; сформированные (адаптированные к росту in vitro) штаммы являются генетически гетерогенными, для них характерно наличие физиологического и генетического гомеостаза, что обусловлено в основном действием стабилизирующего отбора; 3) Культивированные клетки высших растений способны к синтезу практически всех классов соединений вторичного (специализированного) обмена (алкалоиды, стероиды, терпеноиды и др.). Любая соматическая клетка с живым (функционально активным) ядром при ее изолировании и последующем выращивании в условиях культуры тканей вследствие процессов «сомаклональной» изменчивости, происходящих в рамках закона гомологичных рядов в наследственной изменчивости Н. И. Вавилова, может восстановить в своих потомках, в том числе среди растений-регенерантов, весь генетический полиморфизм (или, в крайнем случае, значительную его часть), присущий данному виду, и, вероятно, даже и роду растений, что открывает возможность сохранения и восстановления природного полиморфизма в культуре клеток и тканей in vitro.